Left ventricular chamber geometry in cardiomyopathies: insights from a computerized anatomical study - Juliani, Paulo Sérgio (ESC Heart Fail, 2018)
AIMS: Some authors have hypothesized that left ventricular chamber dilatation in ischaemic and idiopathic cardiomyopathies results in spherical transformation. Aiming to characterize how this transformation occurs, a study was performed by comparing normal and dilated specimens regarding sphericity and proportionality in left heart chambers. It is important to provide data for the development of therapeutic strategies in these diseases. METHODS AND RESULTS: An anatomical study was performed by comparing normal (n = 10), ischaemic (n = 15), and idiopathic (n = 18) dilated human cardiomyopathic specimens regarding left ventricular chambers and their segmental proportionality to normal hearts. It was performed by capturing and processing images with proper software in three different levels of left ventricular chamber (basal, equatorial, and apical). These obtained data were analysed based on sphericity and proportionality by two dedicated indexes. Spherical shape: Calculated segmental indexes showed that dilated specimens were not spherical because they were smaller than as expected for a spherical shape (all values were <70% of a perfect sphere). Proportionality: There was no difference between basal index perimeters among groups, but apical index was lower in dilated specimens than in normal hearts, and so dilatation was not proportional to normal hearts. CONCLUSIONS: Left ventricular chambers of anatomical specimens with dilated cardiomyopathies did not display a spherical shape and were not proportional to normal hearts.